The Value of Holter Monitoring in the Assessment of Non-Specific Symptoms (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: To assess the importance of Holter monitoring in evaluation of non-specific symptoms (like presyncope, dizziness, palpitations, syncope, etc.).Patients and Methods: This is an observational , prospective descriptive study which was conducted at Shaheed Al-Mihrab cardiac centre at Babylon City - Iraq in which 100 patients referred from  the consultation department for the  assessment  of non-specific compliants were included in this study . Holter monitoring was done for all patients after initial evaluation. Holter monitoring was accomplished using GE Holter system with two channels and five leads, attached to the anterior chest wall. The recorder was attached to a strap, which was attached to the patient shoulder. The recording was started in the morning at hospital working hours and the patient was allowed to go home and to resume his normal activities. He was advised to maintain his activity and asked to return  back at the same time next day.Results: 87% of patients have less than 10% premature ventricular ectopics as an isolated event while 90% of the patients have Supraventricular arrythmias less than 10% as isolated events. The mean minimum heart rate was 47 , mean maximum heart rate was 117 and mean average heart rate was 65 . 18 % of patients have ST segment Shift  in which 4% were ST-segment elevation and 14% were ST segment depressions.Conclusion: Holter monitoring was found to have no important role for the early diagnosis of arrhythmias or ischaemia as a cause of compliant in patients with non-specific symptoms